Risk factors for metachronous colorectal cancer following a primary colorectal cancer: A prospective cohort study. Issue 5 (9th May 2016) - Jayasekara, Harindra; Reece, Jeanette C.; Buchanan, Daniel D.; Rosty, Christophe; Dashti, S. Ghazaleh; Ait Ouakrim, Driss; Winship, Ingrid M.; Macrae, Finlay A.; Boussioutas, Alex; Giles, Graham G.; Ahnen, Dennis J.; Lowery, Jan; et al.
Abstract : Individuals diagnosed with colorectal cancer (CRC) are at risk of developing a metachronous CRC. We examined the associations between personal, tumour‐related and lifestyle risk factors, and risk of metachronous CRC. A total of 7, 863 participants with incident colon or rectal cancer who were recruited in the USA, Canada and Australia to the Colon Cancer Family Registry during 1997‐2012, except those identified as high‐risk, for example, Lynch syndrome, were followed up approximately every 5 years. We estimated the risk of metachronous CRC, defined as the first new primary CRC following an interval of at least one year after the initial CRC diagnosis. Observation time started at the age at diagnosis of the initial CRC and ended at the age at diagnosis of the metachronous CRC, last contact or death whichever occurred earliest, or were censored at the age at diagnosis of any metachronous colorectal adenoma. Cox regression was used to derive hazard ratios (HRs) and 95% confidence intervals (CIs). During a mean follow‐up of 6.6 years, 142 (1.81%) metachronous CRCs were diagnosed (mean age at diagnosis 59.8; incidence 2.7/1, 000 person‐years). An increased risk of metachronous CRC was associated with the presence of a synchronous CRC (HR = 2.73; 95% CI: 1.30–5.72) and the location of cancer in the proximal colon at initial diagnosis (compared with distal colon or rectum, HR = 4.16; 95% CI: 2.80–6.18). The presence of a synchronous CRC and the location of the initial CRC might be useful for deciding the intensity of surveillance colonoscopy for individuals diagnosed with CRC. Abstract : What's new? Individuals diagnosed with a colorectal cancer (CRC) are at increased risk of developing a metachronous CRC (a new primary CRC) in the remaining part of the large bowel later in life. Routine stratification of individuals based on their risk for metachronous CRC would allow prevention by surveillance colonoscopy to become cost‐effective. In this prospective cohort study, location of the initial CRC in the proximal colon and presence of a synchronous CRC were associated with an increased risk of metachronous CRC, highlighting their importance when deciding on the intensity of surveillance colonoscopy. There was no evidence for associations between lifestyle and female reproductive factors and metachronous CRC risk.